2015
DOI: 10.1192/bjp.bp.114.153536
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime hypertension as a predictor of brain structure in older adults: cohort study with a 28-year follow-up

Abstract: Long-term exposure to high blood pressure predicts hyperintensities, particularly in deep white matter. The greatest changes are seen in those with severe forms of hypertension, suggesting a dose-response pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
1
27
2
Order By: Relevance
“…Hypertension is the most important risk factor for the development of WMH. 99,180182 Hypertension in general, 180,183185 high SBP, 99,185190 high DBP, 186,189,191193 low DBP, 194 pulse pressure, 185 mean arterial pressure, 195,196 pulse wave velocity, 197 and arterial stiffness 198 have all been associated with WMHs, and it is not clear that one measure of BP predominates over the others in magnitude of the association. Treatment adds considerable complexity to the relationship between hypertension and WMH, but a few clinical trials have shown that WMH progression is reduced with antihypertensive treatment.…”
Section: Hypertension and Admentioning
confidence: 99%
“…Hypertension is the most important risk factor for the development of WMH. 99,180182 Hypertension in general, 180,183185 high SBP, 99,185190 high DBP, 186,189,191193 low DBP, 194 pulse pressure, 185 mean arterial pressure, 195,196 pulse wave velocity, 197 and arterial stiffness 198 have all been associated with WMHs, and it is not clear that one measure of BP predominates over the others in magnitude of the association. Treatment adds considerable complexity to the relationship between hypertension and WMH, but a few clinical trials have shown that WMH progression is reduced with antihypertensive treatment.…”
Section: Hypertension and Admentioning
confidence: 99%
“…51,52 WMHs are likely more common in individuals with stroke, dementia, migraine, 53,54 or late-life depression 55 but not in younger adults with bipolar disease or schizophrenia. 56 In community-based samples, WMH prevalence was low before 55 years of age 57 but increased sharply with age thereafter, from 11% to 21% in the subjects 64 years of age on average to 94% in individuals 82 years of age on average.…”
Section: White Matter Hyperintensitymentioning
confidence: 99%
“…We defined hypertension as elevated BP in a clinical session, physician diagnosis, and/or the use of antihypertensive medication. Such a definition may lead to some misclassification, but this method has been used extensively in the Whitehall II where it produces valid results [41, 42], and similar criteria are employed in other epidemiological studies such as the Atherosclerosis Risk in Communities and Framingham Heart Studies [43, 44]. We did not obtain measures of dietary sodium and potassium that are potentially relevant.…”
Section: Discussionmentioning
confidence: 99%